2023
DOI: 10.24875/rmu.22000052
|View full text |Cite
|
Sign up to set email alerts
|

Experience of WhatsApp uses in the follow-up of pediatric acute lymphoblastic leukemia survivors during the COVID-19 pandemic

Abstract: Experiencia con el uso de WhatsApp en el seguimiento de supervivientes pediátricos de leucemia linfoblástica aguda durante la pandemia por COVID-19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Today, social media play a major role in our lives, drastically changing the way we communicate. Significantly highlighting the follow-up of acute lymphoblastic leukemia patients reported by Fierro-Sáenz et al, 2 achieving an adherence rate of 82.1%.…”
mentioning
confidence: 78%
“…Today, social media play a major role in our lives, drastically changing the way we communicate. Significantly highlighting the follow-up of acute lymphoblastic leukemia patients reported by Fierro-Sáenz et al, 2 achieving an adherence rate of 82.1%.…”
mentioning
confidence: 78%
“…Online consultation is an Internet medical care tool that helped physicians address traditional health services issues during the COVID-19 pandemic and also offered patients a more convenient and cost-effective option to access medical services 2 . Furthermore, a study conducted during the COVID-19 pandemic reported that the use of WhatsApp application aided in the follow-up of patients when social distancing was mandatory 3 . However, there are also potential limitations and multiple difficulties while using social media platforms for medical attention.…”
mentioning
confidence: 99%